Maricha (Piper Nigrum Linn.): An Integrative Review of Ayurvedic Perspectives and Modern Pharmacological Insights - Shubham Khandekar; B.Ram; Premlata; Ekta Shrivastava (International Journal of Ayurveda and Pharma Research, 2025)
Background: Piper nigrum Linn. (Maricha), commonly known as black pepper, is a prominent spice in Ayurvedic pharmacopeia known for its Deepana (appetizing), Pachana (digestive), and Krimighna (anthelmintic) properties. Scientific research increasingly supports its traditional use in treating metabolic, respiratory, and gastrointestinal disorders. Objective: This study presents a comprehensive review of the Ayurvedic significance, classical references, phytochemical composition, and pharmacological activities of Maricha, aiming to bridge traditional wisdom with modern scientific validation. Methods: Extensive literature was reviewed from classical Ayurvedic texts, including Charaka Samhita, Sushruta Samhita, Bhavaprakasha Nighantu, and modern pharmacological research indexed in PubMed, Scopus, and Google Scholar. The phytoconstituents and pharmacological activities were analyzed and summarized based on experimental and clinical findings. Results: Piper nigrum contains alkaloids (notably piperine), essential oils (sabinene, limonene), flavonoids (quercetin, catechin), and minerals. It exhibits antioxidant, anti-inflammatory, anticancer, antimicrobial, lipid-lowering, immunomodulatory, and insecticidal properties. These findings support its use in managing lifestyle disorders and microbial infections. Its classical indications correlate well with its modern pharmacological activities. Conclusion: The integration of classical Ayurvedic understanding with recent pharmacological evidence highlights the therapeutic versatility of Maricha. It holds potential for development into multi-target phytopharmaceutical agents, especially in metabolic and inflammatory diseases.